Does the coupling of the mesospheric semiannual oscillation with the quasi-biennial oscillation provide predictability of Antarctic sudden stratospheric warmings? - Nordström, Viktoria J.; Seppälä, Annika (2021)
During September 2019 there was a sudden stratospheric warming over Antarctica, which brought disruption to the usually stable winter vortex. The mesospheric winds reversed and temperatures in the stratosphere rose by over 50 K. Whilst this was only the second SSW in the Southern Hemisphere (SH), the other having occurred in 2002, its Northern counterpart experiences about six per decade. Currently, an amplification of atmospheric waves during winter is thought to trigger SSWs. However, our understanding remains incomplete, especially in regards to its occurrence in the SH. Here, we investigate the interaction of two equatorial atmospheric modes, the Quasi Biennial Oscillation (QBO) and the Semiannual Oscillation (SAO) during the SH winters of 2019 and 2002. Using MERRA-2 reanalysis data we find that the two modes interact at low latitudes during their easterly phases in the early winter, forming a zero wind line that stretches from the lower stratosphere into the mesosphere. This influences the meridional wave guide, resulting in easterly momentum being deposited in the mesosphere throughout the polar winter, reducing the magnitude of the westerly winds. As the winter progresses these features descend into the stratosphere, until SSW conditions are reached. We find similar behaviour in two other years leading to delayed dynamical disruptions later in the spring. The timing and magnitude of the SAO and the extent of the upper stratospheric easterly QBO signal, that results in the SAO-QBO interaction, was found to be unique in these years, when compared to the years with a similar QBO phase. We propose that this early winter behaviour may be a key physical process in decelerating the mesospheric winds which may precondition the Southern atmosphere for a SSW. Thus the early winter equatorial upper stratosphere-mesosphere together with the polar mesosphere may provide critical early clues to an imminent SH SSW.